THE ROLE OF EMOTIONAL INTELLIGENCE AND SOCIAL ADJUSTMENT IN MARITAL SATISFACTION - Oymatova Dilorom Ruzimurotovna (Scholar Express Journal, 2025)
The study examined the impact of psychological stability of marital relationships, empathy, emotional self-control, and interpersonal communication culture on the level of family satisfaction based on empirical data. The results show that individuals with high levels of emotional intelligence and social adaptation have an advantage in maintaining mutual understanding, sympathy, and emotional stability in family life. The level of emotional intelligence and empathy is manifested as psychological mechanisms that increase marital satisfaction.
Keywords: emotional intelligence; social adaptation; family satisfaction